Use of phase change materials in emergency medical drug transport bags to reduce temperature variability in labile thermal environments - Dingley, John (Anaesthesia)
We wished to know whether low melting point phase change waxes could be used in the manufacture of emergency drug transport bags to reduce the known temperature extremes their contents can be exposed to. We designed 2 custom made hollow-walled drug containers. These were placed within a pair of standard drug transport bags and subjected to 3 day/night cycles including periods of direct radiant sunlight. The wall cavities of one contained air while the wall cavities of the other contained a paraffin wax with a melting point of 44-46°C. This also had a high latent heat of fusion and so until fully melted, its temperature would not increase further. We collected 25,920 temperature data sets at 6 locations within and on the containers. We found that 97.8 % and 84.7 % of ampoule temperatures within the wax and air cavity containers respectively were within a target range of 15°C to 40°C over the study duration (Levene statistic W = 4 279.1; Levene’s test for equality of variance, p < 0.001). Ampoule temperatures in the wax-cavity container only exceeded 40ºC for 1.7 % of the time. Even when they did so, their temperature was limited to a peak of to 40.3ºC, despite an ambient air temperature of >40ºC for 6.4 % of the time (peak 46.9ºC) and a bag surface temperature of >40 ºC for 17.2 % of the time (peak 64.4ºC). In contrast, the ampoule temperature in the air-cavity container exceeded 40ºC for 17.1 % of the time with a peak value of 54.1ºC. We concluded that the latent heat of fusion of phase change materials may be exploited in the design of drug transport bags to mitigate any temperature changes of the drugs stored within them.